Milk Matters: A Literature Review of Pastoralist Nutrition and Programming Responses - Sadler, Kate; Kerven, Carol; Calo, Muriel; Manske, Michael; Catley, Andrew (Tufts Archival Research Center, 2005)
Children across pastoralist/semi pastoralist areas of the horn of Africa are often referred to as some of the most Nutritionally vulnerable in the world. The dominant response from the international community to malNutrition in these areas continues to be the delivery of large quantities of Food relief each time rains fail and rates of acute malNutrition peak. Despite acceptance of the urgent need for risk reduction and drought mitigation there is still little understanding of the causes of malNutrition, and which interventions in the medium to long term should be prioritized to improve the health and Nutritional status of Children--Crimes against in these settings.